The Assessment of the Intangible Resources of the Region as a Component of its Modernization Potential - CHERNOVA, Olga; KOSOLAPOVA, Natal'ja; MATVEEVA, Ludmila; MIKHALKINA, Elena (Journal of Advanced Research in Law and Economics, 2018)
The aim of the article is to present the possibilities of the appliance of factor-approach in evaluation of usage of intangible resources of the region as an important part of its modernization potential. The analysis of theoretical approaches in investigating intangible resources of the region from the perspective of expressing the substantial connection of these resources with the regional modernization strategies provides an opportunity to mark out human, intellectual, informational, organizational and social resources. In the course of development of assessment tools for using the intangible resources of the region as components of its modernization potential two hypotheses were made and confirmed: (1) the proposed groups of intangible resources are possible to be measured by the aggregate of indicators and they can form a system of ‘intangible’ factors of the modernization level of the region economy evaluation; (2) region classification according to the level of intangible resources usage can be made by selected characteristics–indicators. Methods of factorial, correlation and cluster analysis were applied for hypotheses studies. The investigation revealed that all regions have one actual problem. This problem is development of institutional environment which, support commercialization of results of scientific researches. The authors arrived at conclusion about possibility to use developed tools in practice of regional strategizing for uncovering factors, which, form growth and limit modernization development. Also the developed tools can identify strong regions, which are well for realization projects in neo-industrialization sphere.